Sistotrema macabouense (Cantharellales, Hydnaceae), a new corticioid fungus from Martinique - Gruhn, Gérald; Hallenberg, Nils; Courtecuisse, Régis (Phytotaxa, 2017)
A new species Sistotrema macabouense sp. nov., collected in Martinique (French West Indies), is described and illustrated. The differences to closely related species are discussed.